Words Of Turkish Origin In Internet Forums In The Context Of Ethnic Parties - Danczewa, Diliana (Slavica Lodziensia, 2017)
The article presents an interesting linguistic phenomenon from the Bulgarian internet area. The comments under articles, which subjects are Bulgarian political ethnic parties as well as political events in Turkey, contain increased number of words of Turkish origin. They can be classifi ed in several subject groups. Not only lexical means are observed but also word-formation means, such as suffi x -оглу (Биневоглу). The users also are authors of diff erent kind of linguistic innovations, such as phrase innovation (бял кахър – баш кара кахър) or proverbial innovation (Който плаща гранта, той поръчва кючека).